هيئات الرقابة المنشأة بموجب اتفاقيات الامم المتحدة الدولية - خضير وجدان رحم; فضائلي مصطفى (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Considering that the right to equality is the moral safeguard for ensuring other rights without discrimination, regardless of its basis or form, many international instruments have focused on combating discrimination in all its forms through monitoring bodies established under United Nations international conventions